Paraoxonase‐1 activity evaluation as a diagnostic and prognostic marker in horses and foals. (10th March 2020) - Ruggerone, Beatrice; Paltrinieri, Saverio; Giordano, Alessia; Scavone, Donatella; Nocera, Irene; Rinnovati, Riccardo; Spadari, Alessandro; Scacco, Licia; Pratelli, Paola; Sgorbini, Micaela
Abstract: Background: In several species, paraoxonase‐1 (PON‐1) decreases during inflammation, because of the presence of oxidative stress; its measurement recently has been validated in horses, but its role as a clinical biomarker is unknown. Objectives: To evaluate sensitivity, specificity and likelihood ratio of PON‐1 activity to identify systemic inflammatory response syndrome (SIRS)‐positive horses or horses with a poor prognosis. Animals: One hundred seventy‐two blood samples from 58 sick horses from 3 different veterinary hospitals. Methods: In a cross‐sectional study, PON‐1 activity was measured upon admission and at 24‐hour intervals until discharge or death, and results were analyzed based on SIRS status and outcome. Results: No statistically significant difference was found in median PON‐1 activity between SIRS and non‐SIRS cases or between survivors and non‐survivors except for mares, in which PON‐1 activity was significantly lower in SIRS‐positive horses ( P = .05). The sensitivity of PON‐1 activity in identifying horses with SIRS or negative outcome was low (0.0%‐46.2% depending on the examined group) but its specificity was high (87.0%‐100.0%). However, when PON‐1 is low, the likelihood of death is 2.40‐3.89 times higher than the likelihood of survival. Repeated measurement of PON‐1 after treatment does not predict outcome. Conclusions and Clinical Importance: Evaluation of PON‐1 activity in horses with inflammation might be advisable in the future, but only low activity at admission may be relevant in predicting SIRS or negative outcome.